Market Orientation, Competitive Environment, and Value Creation in Private Higher Education: Evidence from Palembang During COVID-19 - Ahmad Maulana; Catharina Clara; Nurkardina Novalia (Binus Business Review, 2025)
The research addressed a gap in the literature by examining how market orientation and competitive environment jointly influenced value creation and marketing performance in private Higher Education Institutions (HEIs), a relationship that remained underexplored, particularly in emerging economies during the COVID-19 recovery period. While previous studies had examined market orientation or competitive factors in isolation, few had integrated these constructs with the mediating role of value creation in the context of service marketing for HEIs. Data were collected through purposive sampling from 225 students enrolled in private universities in Palembang, South Sumatra, Indonesia, between July and September 2023. Ordinary Least Squares (OLS) regression was employed due to the observed variables, relatively small sample size, and the need for a parsimonious model estimation. The findings show that the competitive environment significantly enhances value creation, whereas market orientation does not significantly affect value creation. Market orientation has a direct positive impact on marketing performance, while the competitive environment exerts a negative influence. Moreover, value creation partially mediates the relationship between competitive environment and marketing performance, but not between market orientation and marketing performance. These results highlight the strategic role of value creation in navigating environmental challenges and sustaining marketing effectiveness. The research contributes to the literature by integrating competitive environment into the market orientation–performance framework in the under-researched context of Indonesian private HEIs. It also offers practical implications for institutional leaders to align their strategic orientation with value-driven initiatives to enhance competitiveness.